2004
DOI: 10.1111/j.1752-1688.2004.tb01014.x
|View full text |Cite
|
Sign up to set email alerts
|

HYDROLOGICAL AND GEOCHEMICAL TRENDS AND PATTERNS IN THE UPPER RIO GRANDE, 1975 TO 19991

Abstract: Hydrological and geochemical spatial patterns and temporal trends were analyzed using U.S. Geological Survey (USGS) water quality data collected from 1975 to 1999 along the uppermost 600 km of the Rio Grande in Colorado and New Mexico. Data on discharge, specific conductivity (SC), total dissolved solids (TDS), pH, Ca2+, Na+, Mg2+, K+, HCO3−, SO42‐, Cl−, F−, and SiO2 came from six USGS stations ranging from the Colorado‐New Mexico border to below Albuquerque, New Mexico. Linear regression, Kendall's S, and Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…The ephemeral Rio Puerco and Rio Salado and intermittent Jemez River are the three major tributaries within the Middle Rio Grande, however they contribute little water to the river [Moore and Anderholm, 2002]. Annual discharge from the Albuquerque wastewater treatment plant to the Rio Grande makes it one of the largest tributaries in the river's upper basin [Passell et al, 2004].…”
Section: Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ephemeral Rio Puerco and Rio Salado and intermittent Jemez River are the three major tributaries within the Middle Rio Grande, however they contribute little water to the river [Moore and Anderholm, 2002]. Annual discharge from the Albuquerque wastewater treatment plant to the Rio Grande makes it one of the largest tributaries in the river's upper basin [Passell et al, 2004].…”
Section: Site Descriptionmentioning
confidence: 99%
“…We calculated average monthly concentration values for the river and LFCC to compare with the model results using surface water data from the USGS NWIS online database [U.S. Geological Survey (USGS), 2006] (Figure 4). We chose to use data after 1993 based on work by Passell et al, [2004] which suggested that significant improvements were made to the Albuquerque WWTP that reduced nitrate concentrations in the river around this time. Therefore, while the model runs from 1975 -2005, we only compared modeled and observed data between 1993 and 1995.…”
Section: Model Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of water quality parameters time series allows the observation of variability in load and concentration over time, which helps to identify the main impact factors and polluting potentials occurring around the area in analysis. Over the last years, many studies have been performed around the world aiming to detect trends and changes in water quality (PASSELL;DAHM;BEDRICK, 2004;CHANG, 2008;CHRISTOFARO;LEÃO, 2009;TABARI;MAROFI;AHMADI, 2011;GOCIC;TRAJKOVIC, 2013;SUN et al, 2013;TRINDADE, 2013;BARBOSA, 2015). The time series studied by these authors vary significantly depending on the availability of data, and some of them call for longer monitoring periods in order to obtain more reliable findings.…”
Section: Introductionmentioning
confidence: 99%